Has monetary policy been so bad that it is better to get rid of it? The case of Mexico - Marco Del Negro; Francesc Obiols-Homs (Federal Reserve Bank of Atlanta, 2000)
Motivated by the dollarization debate in Mexico, we estimate an identified vector autoregression for the Mexican economy using monthly data from 1976 to 1997, taking into account the changes in the monetary policy regime which occurred during this period. We find that 1) exogenous shocks to monetary policy have had no impact on output and prices, 2) most of the shocks originated in the foreign sector, 3) disturbances originating in the U.S. economy have been a more important source of fluctuations for Mexico than shocks to oil prices. We also study the endogenous response of domestic monetary policy by means of a counterfactual experiment. The results indicate that the response of monetary policy to foreign shocks played an important part in the 1994 crisis.
Keywords: 330; Mexico; Monetary policy; Dollarization